The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/er.4912
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of biogas/air combustion by hydrogen addition at elevated temperatures

Abstract: Summary In this study, combustion characteristics of various biogas/air mixtures with hydrogen addition at elevated temperatures were experimentally investigated using bunsen burner method. Methane, CH4, was diluted with different concentrations of carbon dioxide, CO2, 30 to 40% by volume, to prepare the biogas for testing. It is followed by the hydrogen, H2, enrichment within the range of 0 to 40% by volume and the temperature elevation of unburned gas till 440 K. Blowoff velocities were measured by lowering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…Other studies revealed the effect of additives (N 2 , Ar, H 2 O or CO 2 ) on CH 4 /air, CH 4 /CO 2 /air and CH 4 /O 2 /H 2 /inert flames [35][36][37][38][39][40][41]. The attention of other researchers has been directed towards the combustion characteristics of biogas under hydrogen-enriched conditions [24,[42][43][44][45][46][47][48][49]. In some experiments, realised in a spark ignition engine, small H 2 amounts were added to biogas to enhance engine performance and reduce pollutant emissions [16,[50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies revealed the effect of additives (N 2 , Ar, H 2 O or CO 2 ) on CH 4 /air, CH 4 /CO 2 /air and CH 4 /O 2 /H 2 /inert flames [35][36][37][38][39][40][41]. The attention of other researchers has been directed towards the combustion characteristics of biogas under hydrogen-enriched conditions [24,[42][43][44][45][46][47][48][49]. In some experiments, realised in a spark ignition engine, small H 2 amounts were added to biogas to enhance engine performance and reduce pollutant emissions [16,[50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…The effect hereof is characterized by two factors: the curvature of the flame tip and the disproportion of molecular diffusion of the components of the mixture. However, the effect is more apparent at higher concentrations of hydrogen [108].…”
Section: Figurementioning
confidence: 91%
“…This can, however, be expected, considering the increased flame speed of hydrogen when compared to natural gas [40]. In a study by Nurmukan et al, combustion characteristics, such as the occurrence of blow-offs (high fuel flow velocity that extinguishes the flame) and burning velocities, were examined for biogas/hydrogen mixtures [108]. Figure 4 presents the images of the biogas/hydrogen flames with hydrogen concentrations in the range of 0-40 vol% at the same inlet velocity (top) and the images of the flames at various inlet velocities before blow-off (bottom).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Although there are multiple breakthroughs in the understanding of combustion characteristics of hydrogen enriched flames in multiple research devices, the applicability of this knowledge is still in its early stage. While there are plenty of research works related to constantvolume chambers, 26,27 scaled burners, 28 or rapid compression machines 29 ; the state-of-the-art in H 2 ICE is more limited and mostly focused on developing engines fueled by pure hydrogen. 30 Nonetheless, this approach is still difficult to implement for commercial transportation in passenger cars due to severe economic constraints.…”
mentioning
confidence: 99%